Corporate Governance and Corporate Social Responsibility Synergies: A Systemic Approach - Nikolić , Jelena; Zlatanović, Dejana (Naše gospodarstvo/Our economy, 2018)
Respecting the importance of corporate governance (CG), particularly various corporate governance mechanisms for improving corporate social responsibility (CSR) activities, the paper highlights relevant CG–CSR synergies from the perspective of systems thinking. The paper further aims to demonstrate the ways in which selected systems methodologies can support CG–CSR synergies. Accordingly, we selected appropriate systems methodologies, such as dialectical systems theory, soft systems methodology, and system dynamics. We defined the dialectical system, consisting of essential corporate governance mechanisms, which contribute to CSR; we also identified the key stakeholders and their perceptions of CG–CSR relations through CATWOE analysis; thus, the appropriate root definition and conceptual model, including the activities that are relevant for CG–CSR relations, were developed. Developed systemic framework provided a relevant methodological support to highlight the various issues of corporate governance, such as institutional framework, market for corporate control, ownership structure, board structure, and their contribution to CSR.